Enabling Inclusive Development Concept in Marginalized Settlement Community (Case Study: Kampung Jodipan, Kota Malang) - Kurniasari, Merisa; Hayati, Arina; Setijanti, Purwanita (IPTEK Journal of Proceedings Series, 2020)
The era of democratization requires city leaders to change the development paradigm to be inclusive. This is stated in goal number 11 of the SDGs document, "making cities and human settlements inclusive, safe, resilient, and sustainable", so this study tries to look at the concept of inclusiveness in the scope of settlements, especially in marginal settlements. This study takes place in marginal settlements in the Brantas watershed as Kampung Jodipan which was once a slum settlement but now has been transformed into a Kampung tourism. This openness applies the principle of inclusiveness of the Kampung Jodipan. The data of this research were analyzed with descriptive statistics using Factor Analysis and Cross Tabulation, then the data was validated using triangulation analysis. This study aims to highlight the experience of Kampung Jodipan as a marginal settlement that has succeeded in improving Kampung. It was found that the inclusiveness dimensions in Kampung Jodipan were social inclusion and physical inclusion. Socially, the embodiment of the inclusiveness can be seen through the trust of the community and involving the residents in various activities. Meanwhile, the concept of spatial inclusiveness is manifested with the inclusion of basic infrastructure as a means of meeting the daily needs of citizens.